2019
DOI: 10.1159/000502914
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Roles of ROCK1 and ROCK2 on the Cerebral Ischemia Injury and Subsequently Neurodegenerative Changes

Abstract: Cerebral ischemic injury is one of the main causes of adult disability and death. Although significant progress has been made, cerebral ischemia continues to be a major risk to public health worldwide. The Rho kinase (ROCK) signaling pathway has been reported to be significantly involved in many mechanisms of cerebral injury. Although ROCK is ubiquitously expressed in all tissues, ROCK2 subtype expression in brain and the spinal cord is more abundant and improves with age. This makes it a promising target for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…ROCK1 and ROCK2 have different functions in various types of cells and tissues. 47,48 In our study, when CTNNAL1 was silenced, the expression of ROCK1 decreased while ROCK2 increased both in vitro and in vivo. We found that CTNNAL1 deficiency significantly increased ROCK2 expression after HDM stimulation.…”
Section: Discussionmentioning
confidence: 47%
“…ROCK1 and ROCK2 have different functions in various types of cells and tissues. 47,48 In our study, when CTNNAL1 was silenced, the expression of ROCK1 decreased while ROCK2 increased both in vitro and in vivo. We found that CTNNAL1 deficiency significantly increased ROCK2 expression after HDM stimulation.…”
Section: Discussionmentioning
confidence: 47%
“…Moving to genes altered in early stage of DR, except for one study on IGSF21 (Immunoglobin Superfamily Member 21) (Lin et al, 2016), none of the genes have been studied in context to DR. However, ROCK2 (Rho Associated Coiled-Coil Containing Protein Kinase 2) (Koch et al, 2014;Lu et al,…”
Section: Discussionmentioning
confidence: 99%
“…The identified early genes were found to be involved in one or more crucial events associated with DR progression like angiogenesis, oxidative stress, inflammation, etc. Further, some of the early genes like ROCK2 (Koch et al, 2014;Lu et al, 2020), UHRF1 (Ramesh et al, 2016), and MAPT (C. C. Zhang et al, 2016) are shown to participate in neurodegeneration, which is one of the earliest events in DR development. Also, in the present study, one of the identified early genes, i.e., NR1H4, was also found to be the target of one of the downregulated miRNAs (has-mir-192) identified in plasma sample of NPDR cases.…”
Section: Genes Involved In Early Stage Of Drmentioning
confidence: 99%
“…p190RhoGAP is initially reported to RhoA negatively regulator and recently the dysregulation of RhoGAPs is thought to be related with CNS disease (Huang et al, 2017) and ROCK1 is downstream target of RhoA (Kümper et al, 2016;Lu et al, 2020).…”
Section: Crtc2 Regulates P190rhogap Expressionmentioning
confidence: 99%